Determination of habitat characteristics associated with the presence of ninphas of Ocoaxo assimilis - Cuellar Rodriguez, Gerardo; Cid Muñoz, Raquel; Cervantes Espinoza, Montserrat; Armendáriz Toledano, Francisco; Reyna González, Mario (Ecosistemas y Recursos Agropecuarios, 2025)
This study examines the relationship between floristic composition, habitat characteristics and edaphic factors associated with the presence of Ocoaxo assimilis nymphs in Pino-Encino forests in Puebla, Mexico. Using a multidimensional approach that integrated systematic quadrat sampling, logistic regression analysis, nonparametric tests (Mann-Whitney U and Kruskal-Wallis), and similarity analysis methods (ANOSIM, NMDS), key variables influencing nymph distribution were identified. Logistic regression models revealed that nymphs prefer sites at higher altitudes and with greater floristic diversity, particularly those with arboreal indicator species such as Quercus rugosa and Quercus mexicana, as well as the herbaceous Euphorbia sp. and Verbena sp. The absence of Senegalia greggii was also found to be an essential factor. Although edaphic factors did not show significant differences, it was suggested that clay content might have an indirect role in habitat preference. These results provide new insights into ecological interactions in these ecosystems and establish a basis for developing monitoring and management strategies aimed at forest integrity.